2023
DOI: 10.1177/15210251231163837
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Shock and Resilience: How Transfer-Related GPA Drop and Rebound Predict Student Departure from a Flagship University Campus

Abstract: As they navigate the social and academic expectations of a new college, transfer students commonly suffer “transfer shock,” or a sudden drop in GPA. However, little is known about why some students suffer transfer shock, why some bounce back, and the consequences in terms of student retention. This analysis of over 25,000 transfer students (N = 25,000) at a large flagship university finds an average first-term drop of −0.30 GPA points, but the impact of this shock on student departure is dependent on initial G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…The lack of a high frequency of transfer shock suggests that the term transfer shock may be ill-advised because it may imply that transfer students' GPAs generally decrease in the first posttransfer semester (Gentsch et al, 2022), as many bachelor's-college faculty believe (Rabinowitz et al, 2023). As in Jaggars et al (2023), our findings did show that the greater the transfer shock, the less likely students were to persist in a bachelor's program and to graduate with a bachelor's degree.…”
Section: Variables Associated With the Leakssupporting
confidence: 49%
See 1 more Smart Citation
“…The lack of a high frequency of transfer shock suggests that the term transfer shock may be ill-advised because it may imply that transfer students' GPAs generally decrease in the first posttransfer semester (Gentsch et al, 2022), as many bachelor's-college faculty believe (Rabinowitz et al, 2023). As in Jaggars et al (2023), our findings did show that the greater the transfer shock, the less likely students were to persist in a bachelor's program and to graduate with a bachelor's degree.…”
Section: Variables Associated With the Leakssupporting
confidence: 49%
“…Other studies, however, have not found strong evidence of transfer shock (e.g., Aulck & West, 2017). A recent study of more than 25,000 students who had transferred to a large, flagship university, almost three quarters of whom were White, found that 63% of the sample experienced a GPA drop (transfer shock) in the semester following transfer, and the larger the GPA drop, the more likely a student was to leave college (Jaggars et al, 2023).…”
Section: Malleable Factors Related To Posttransfer Pipeline Stagesmentioning
confidence: 99%